Effectiveness of a management program for outpatient clinic or remote titration of beta-blockers in CRT patients: The RESTORE study. (1st June 2017) - D'Onofrio, Antonio; Palmisano, Pietro; Rapacciuolo, Antonio; Ammendola, Ernesto; Calò, Leonardo; Ruocco, Antonio; Bianchi, Valter; Maresca, Fabio; Del Giorno, Giuseppe; Martino, Annamaria; Mauro, Ciro; Campari, Monica; et al.
Abstract: Background: Many patients fail to receive β-blockers before cardiac resynchronization therapy defibrillator (CRT-D) implantation, or receive them at a suboptimal dose, and require optimization after implantation. We assessed the effectiveness of a structured program for β-blocker titration in CRT-D patients followed up by means of conventional in-clinic visits or remote monitoring. Methods and results: 130 patients undergoing CRT implantation and treated according to the standard practice of the centers were included as a control group. A second group of 124 CRT-D candidates (Study Group) underwent up-titration visits every 2 weeks after implantation (target dose: 10 mg/day of bisoprolol or 50 mg/day of carvedilol). In the Study Group, remote monitoring was undertaken in 66 patients, who received additional equipment for daily transmission of weight and blood pressure data, and scheduled titration telephone calls. In the Control Group, the maximal dose of β-blockers was being administered to 12 (9%) patients on implantation and 21 (16%) on 6-month follow-up examination ( p  > 0.05). In the Study Group, 25 (20%) patients were receiving the maximal dose of β-blockers on implantation and 72 (58%) on follow-up examination ( p  < 0.001). The 66 Study Group patients on remote monitoring underwent fewer in-clinic visits ( p  = 0.034). Of these, 50 (76%) were on the maximal dose after remote up-titration (versus 38% of patients followed up conventionally, p  < 0.001). The decrease in left ventricular end-systolic volume was larger in the Study Group ( p  = 0.040). Conclusions: The program for β-blocker up-titration increased the number of patients reaching the target dose and improved the response to the therapy. The use of remote monitoring and daily transfer of weight and blood pressure data facilitated β-blocker titration. Clinical trial registration: URL:http://clinicaltrials.gov / Identifier:NCT02173028 .